Konstruksi Formula Produksi Maslahah Indikator Maqasid Al-Shari’ah Sebagai Konstruktor Nilai Berkah - Nurlaili Adkhi Rizfa Faiza (JES (Jurnal Ekonomi Syariah), 2020)
In Islam, Not only the production requires physical attributes, but also the value of barakah. Because without the value of barakah, the production process will not be productive. But the value of barakah here cannot be calculated conclusively because of the blessing of its origin from God because the production factors in Islam are also determined by the concept of mas}lah}ah (containing benefits), by following with the demands of maqa>s}id al-shari>’ah, which leads to barakah, thus formulated the blessing value of the maqa>s}id al-shari>’ah indicator which includes h}ifz} al-di>n (orientation of worship), h}ifz} al-nafs (internal process orientation), h}ifz} al-nasl (labor orientation), h}ifz} al-‘aql (learner orientation), and h}ifz} al-ma>l (orientation of wealth). This research aims to create quantitative formulations of the indicator.This reference used research method. Author obtains result of mas}lah}ah production level, which calculated by production rate of an item depends on amount of capital, labor, natural wealth, and level of the technology used. as well as the value of blessing. If five factors have been realized, then the optimum production value with the benefit of the hereafter can be achieved. Keywords: barakah; maqa>s}id al-shari>’ah; mas}lah}ah